Applying Halliday’s Transitivity Theory to the Joe Biden’s First Annual Speech: Menerapkan Teori Transitivitas Halliday pada Pidato Tahunan Pertama Joe Biden - Pratiwi Harsa , Wiwien (UPMI Proceeding Series, 2023)
The goals of this study are to investigate and describe what kinds of transitivity processes were proposed by Halliday and how they reveal in Joe Biden’s first annual speech. The data in this study comes from the textual script of Joe Biden’s speech on a web page. The descriptive qualitative method was used in this study, as well as data-gathering strategies such as observation and documentation. The procedures of identifying, classifying, and analyzing were used to analyze the data. There are five types of transitivity processes found by the researcher, namely mental process, material process, verbal process, relational process, and existential process as the results of this study where the findings show that mental processes appear the most in the script of Joe Biden’s first annual public speech with a portion of 44.75%, amounting to 81 times the utterances appeared. It also means that Joe Biden’s leadership involves a lot of affection processes related to feelings or senses, as evidenced by the mental processes that appear the most in the annual speech.